Materials Sustainability in the Pharmaceutical Industry - Bhadoriya, Ankita; Patil, Bhakti; Vinchurkar, Kuldeep; Mane, Sheetal; Parambath, Anilkumar (Sustainability & Circularity NOW, 2024)
In the pharmaceutical industry, sustainable materials development is increasingly vital. The environmental impacts of medications emerge across their entire life cycle. While the pharmaceutical industry plays a crucial role in minimizing these effects during early production stages, opportunities to reduce environmental impacts stemming from drug consumption and disposal are currently limited. The pharmaceutical industry faces growing pressure to integrate sustainable practices into its operations due to environmental concerns and regulatory requirements. Materials sustainability, focusing on the responsible use of resources and minimizing environmental impact, has emerged as a crucial aspect of this transformation. Key strategies include the adoption of green chemistry principles to reduce hazardous substances and waste generation during drug development and manufacturing processes. Biodegradable materials and eco-friendly packaging designs are increasingly favored to mitigate the industry's impact on landfills and ecosystems. Challenges remain, including the complexity of regulatory frameworks and the need for collaborative efforts across stakeholders to achieve meaningful progress in material sustainability. This review is an attempt to present materials sustainability in the pharmaceutical industry and its pivotal shift toward environmentally responsible practices, driven by innovation, and regulation, aimed to investigate current environmental initiatives within the industry, alongside perspectives and attitudes regarding strategies to tackle environmental challenges and concerns. Sustainability in the pharmaceutical industry requires a holistic and integrated approach, involving every aspect of the business, from supply chain management to product development. By prioritizing sustainability, the industry can contribute to global climate goals while ensuring its own resilience and long-term success.
Keywords: Sustainability; Regulation; Pharmaceuticals in the environment; Pharmaceutical industry; Environmental classification; Green chemistry